Multilayered membranes with tuned well arrays to be used as regenerative patches. (15th July 2017) - Martins, Nádia I.; Sousa, Maria P.; Custódio, Catarina A.; Pinto, Vânia C.; Sousa, Paulo J.; Minas, Graça; Cleymand, Franck; Mano, João F.
Graphical abstract: Abstract: Membranes have been explored as patches in tissue repair and regeneration, most of them presenting a flat geometry or a patterned texture at the nano/micrometer scale. Herein, a new concept of a flexible membrane featuring well arrays forming pore-like environments to accommodate cell culture is proposed. The processing of such membranes using polysaccharides is based on the production of multilayers using the layer-by-layer methodology over a patterned PDMS substrate. The detached multilayered membrane exhibits a layer of open pores at one side and a total thickness of 38 ± 2.2 µm. The photolithography technology used to produce the molds allows obtaining wells on the final membranes with a tuned shape and micro-scale precision. The influence of post-processing procedures over chitosan/alginate films with 100 double layers, including crosslinking with genipin or fibronectin immobilization, on the adhesion and proliferation of human osteoblast-like cells is also investigated. The results suggest that the presence of patterned wells affects positively cell adhesion, morphology and proliferation. In particular, it is seen that cells colonized preferentially the well regions. The geometrical features with micro to sub-millimeter patterned wells, together with the nano-scale organization of the polymeric components along the thickness of the film will allow to engineer highly versatile multilayered membranes exhibiting a pore-like microstructure in just one of the sides, that could be adaptable in the regeneration of multiple tissues. Statement of Significance: Flexible multilayered membranes containing multiple micro-reservoirs are found as potential regenerative patches. Layer-by-layer (LbL) methodology over a featured PDMS substrate is used to produce patterned membranes, composed only by natural-based polymers, that can be easily detached from the PDMS substrate. The combination of nano-scale control of the polymeric organization along the thickness of the chitosan/alginate (CHT/ALG) membranes, provided by LbL, together with the geometrical micro-scale features of the patterned membranes offers a uniqueness system that allows cells to colonize 3-dimensionally. This study provides a promising strategy to control cellular spatial organization that can face the region of the tissue to regenerate.